ANALISIS NILAI HASIL TERHADAP WAKTU MENGGUNAKAN SOFTWARE MICROSOFT PROJECT (STUDI KASUS PADA PROYEK PEMBANGUNAN KONSTRUKSI GEDUNG KANTOR KPU KABUPATEN MAJALENGKA): Indonesia - Rijaluddin, Arief; Awit Wijayanti (Universitas Majalengka, 2023)
The rapid of economic growth in Indonesia, of course, accompanied by the increasing public demand for construction projects. Each project has a different goal, in the implementation of the General Election Commission Office Building Construction Project which is planned for 143 calendar days, namely in the period 10th August 2020 to 31st December 2020 by the Contractor PT. Kalimasada Zahraa Jaya with a project value of Rp. 4.306.705.600,- In the process of achieving these goals, a good construction management is needed so that the project is in accordance with the plan. In this case, the Earned Value Analysis method is used to determine if there is a discrepancy in the implementation of the project. The data analysis process uses Microsoft Project software for project scheduling and human resource allocation for each element of work effectively and efficiently. The data analyzed include presenting S curve graph data, calculating the schedule variance